EXPLORATION OF ACCOUNTING PRINCIPLES APPLICATION IN GENERATION Z STUDENTS’ FINANCIAL MANAGEMENT AS E-COMMERCE CONSUMERS - Septia Kyna Fedora; Bambang Minarso (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
This study examines how online shopping affects the personal financial management of Generation Z university students. Using a qualitative method, in-depth interviews were conducted with students from accounting academic backgrounds to explore their online shopping habits, financial management behaviors, and how they apply accounting principles in daily life. The data were analyzed thematically to identify recurring patterns and unique insights. The results indicate that online shopping provides convenience, wider product choices, and often lower prices, but also encourages impulsive spending due to frequent discounts, flash sales, and promotions. While some students have started tracking and categorizing their expenses, many have yet to fully apply accounting principles in managing their finances. Moreover, there is a noticeable gap between the accounting knowledge gained in class and its practical use in everyday financial decisions. These findings highlight the importance of strengthening financial literacy among students through both formal education and practical tools. Based on the study, it is recommended to develop personal finance applications that include features like expense tracking, budget limits, and spending analysis to help students manage their money more effectively. In addition, the principles of integrity, transparency, responsibility, and accountability should be nurtured from an early age, so that financial discipline and ethical awareness can develop naturally as students grow. The insights gained here could guide the creation of financial tools and strategies that better support responsible money management among university students